2008
DOI: 10.1002/pmic.200800127
|View full text |Cite
|
Sign up to set email alerts
|

SIMS and MALDI MS imaging of the spinal cord

Abstract: The application of mass spectrometry to imaging, or MS imaging (MSI), allows for the direct investigation of tissue sections to identify biological compounds and determine their spatial distribution. We present an approach to MSI that combines secondary ion mass spectrometry (SIMS) and MALDI MS for the imaging and analysis of rat spinal cord sections, thereby enhancing the chemical coverage obtained from an MSI experiment. The spinal cord is organized into discrete, anatomically defined areas that include moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…The FA detected and here described as masses specific to the OA condition, could be part of these lipids. Future parallel studies using MALDI-imaging for instance, could discriminate these intact lipids as other authors have shown (33)(34)(35).…”
Section: Pca Revealed the Presence Of Droplets Rich In Lipids In Oa Cmentioning
confidence: 94%
“…The FA detected and here described as masses specific to the OA condition, could be part of these lipids. Future parallel studies using MALDI-imaging for instance, could discriminate these intact lipids as other authors have shown (33)(34)(35).…”
Section: Pca Revealed the Presence Of Droplets Rich In Lipids In Oa Cmentioning
confidence: 94%
“…E.g., a selection of [1,4,5] usually results in the retrieval of a single scalar corresponding to the item with index (1,4,5).…”
Section: Data Selection Basic Slicingmentioning
confidence: 99%
“…That is all elements in the selection specified for x are combined with the selection specified for y. x=1:4 and y=1:3, hence, results in the retrieval of the elements [(1,1), (1,2), (2,1), (2,2) (3,1), (4,2)]. All-to-all selection, hence, always result in the retrieval of of a single or multiple rectangular regions.…”
Section: Multi-dimensional Slicingmentioning
confidence: 99%
See 2 more Smart Citations